Pharmacologically controlling protein-protein interactions through epichaperomes for therapeutic vulnerability in cancer - Suhasini Joshi (Nature Portfolio, 2021)
Joshi, Gomes et al. employ a chemical modulation approach of the cellular interactome to a hyperconnectivity state and show association with the increased response of pancreatic cancer cell lines to specific drugs, including those that target the MAPK-pathways and PI3K-mTOR pathway. To achieve this, the authors employ chemical modulation of the interactome via epichaperome inhibition with the small molecule PU-H71.